High sensitivity flow cytometry of membrane vesicles. (20th October 2015) - Stoner, Samuel A.; Duggan, Erika; Condello, Danilo; Guerrero, Abraham; Turk, James R.; Narayanan, Padma K.; Nolan, John P.
Abstract: Extracellular vesicles (EVs) are attracting attention as vehicles for inter‐cellular signaling that may have value as diagnostic or therapeutic targets. EVs are released by many cell types and by different mechanisms, resulting in phenotypic heterogeneity that makes them a challenge to study. Flow cytometry is a popular tool for characterizing heterogeneous mixtures of particles such as cell types within blood, but the small size of EVs makes them difficult to measure using conventional flow cytometry. To address this limitation, a high sensitivity flow cytometer was constructed and EV measurement approaches that allowed them to enumerate and estimate the size of individual EVs, as well as measure the presence of surface markers to identify phenotypic subsets of EVs. Several fluorescent membrane probes were evaluated and it was found that the voltage sensing dye di‐8‐ANEPPS could produce vesicle fluorescence in proportion to vesicle surface area, allowing for accurate measurements of EV number and size. Fluorescence‐labeled annexin V and anti‐CD61 antibody was used to measure the abundance of these surface markers on EVs in rat plasma. It was shown that treatment of platelet rich plasma with calcium ionophore resulted in an increase in the fraction of annexin V and CD61‐positive EVs. Vesicle flow cytometry using fluorescence‐based detection of EVs has the potential to realize the potential of cell‐derived membrane vesicles as functional biomarkers for a variety of applications. © 2015 International Society for Advancement of Cytometry